2017
DOI: 10.1002/slct.201600929
|View full text |Cite
|
Sign up to set email alerts
|

One–pot Reaction for the Convenient Synthesis of Functionalized 2‐Oxaspiro[bicyclo[2.2.1]heptane‐2,3′‐indolines]

Abstract: An efficient synthetic protocol for functionalized 2-oxaspiro [bicyclo[2.2.1]heptane-2,3'-indolines] was successfully developed by one-pot two-step reaction of phenacyl bromides, malononitrile and 3-methyleneoxindolines in ethanol in the presence of triethylamine. On the other hand, the similar threecomponent reaction of phenacyl bromides, ethyl cyanoacetate and 3-methyleneoxindolines afforded functionalized spiro[cyclopentane-1,3'-indoline] derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…The mechanism of the rst step including b-ketodinitriles formation is known. [32][33][34][35][36][37][38]…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of the rst step including b-ketodinitriles formation is known. [32][33][34][35][36][37][38]…”
Section: Resultsmentioning
confidence: 99%
“…To explain the formation of different cyclic compounds, a domino reaction mechanism was proposed as shown in Scheme 2 on the basis of previous work 5 and the present experiments. In the presence of a base, a carbanion ( A ) was in situ generated by deprotonation.…”
Section: Resultsmentioning
confidence: 89%
“…3,4 For example, Estevez and coworkers successfully found the intramolecular alkylation of methyl-5- O -benzyl-3,6-deoxy-6-nitro-α- d -glucofuranoside into the corresponding 2-oxabicyclo[2.2.1]heptane derivatives (eqn (1) in Scheme 1). 5 a Ramachary and coworkers found that the unique 5-oxaspiro[bicyclo[2.2.1]heptane-2,3′-indolin]-2′-ones can be obtained in excellent diastereoselectivity (dr > 99 : 1) by double reduction of olefin and carbonyl groups with NaBH 4 (eqn (2) in Scheme 1). 5 b In this respect, we successfully found that the base promoted domino reaction of malononitrile with two molecules of 3-phencylideneoxindoles resulted in novel 7-(2-oxoindolin-3-yl)-2-oxaspiro[bicyclo[2.2.1]heptane-6,3′-indolines] in various diastereoselectivities (eqn (3) in Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, phenacylmalononitrile is also a readily available substrate, which can be easily prepared through a base-promoted substitution reaction of phenacyl bromide with malononitrile under mild conditions [11][12][13][14][15][16]. In many practical cases, phenacylmalononitriles could be conveniently generated in situ by directly using a mixture of phenacyl bromide and malononitrile in the reaction system [17][18][19][20][21][22]. As a consequence, the unique features of phenacylmalononitriles make them good candidates for the efficient construction of diverse carbocyclic and heterocyclic compounds [23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%